A pilot validation of multi‐echo based echo‐planar correlated spectroscopic imaging in human calf muscles. (6th August 2014) - Furuyama, Jon K.; Nagarajan, Rajakumar; Roberts, Christian K.; Lee, Cathy C.; Hahn, Theodore J.; Thomas, M. Albert
<x xml:space="preserve">Abstract</x> A current limitation of MR spectroscopic imaging of multiple skeletal muscles is prolonged scan duration. A significant reduction in the total scan duration using the echo‐planar correlated spectroscopic imaging (EP‐COSI) sequence was accomplished using two bipolar readout trains with different phase‐encoded echoes for one of two spatial dimensions within a single repetition time (TR). The second bipolar readout was used for spatially encoding the outer k‐space, whereas the first readout was used for the central k‐space only. The performance of this novel sequence, called multi‐echo based echo‐planar correlated spectroscopic imaging (ME‐EPCOSI), was demonstrated by localizing specific key features in calf muscles and bone marrow of 11 healthy volunteers and five subjects with type 2 diabetes (T2D). A 3 T MRI–MRS scanner equipped with a transmit–receive extremity coil was used. Localization of the ME‐EPCOSI sequence was in good agreement with the earlier single‐readout based EP‐COSI sequence and the required scan time was reduced by a factor of two. In agreement with an earlier report using single‐voxel based 2D MRS, significantly increased unsaturated pools of intramyocellular lipid (IMCL) and extramyocellular lipid (EMCL) and decreased IMCL and EMCL unsaturation indices (UIs) were observed in the soleus and tibialis anterior muscle regions of subjects with T2D compared with healthy controls. In addition, significantly decreased choline content was observed in the soleus of T2D subjects compared with healthy controls. Multi‐voxel characterization of IMCL and EMCL ratios and UI in the calf muscle may be useful for the non‐invasive assessment of altered lipid metabolism in the pathophysiology of T2D. Copyright © 2014 John Wiley & Sons, Ltd.